2014
DOI: 10.1002/jso.23787
|View full text |Cite
|
Sign up to set email alerts
|

MFH and high-grade undifferentiated pleomorphic sarcoma-what's in a name?

Abstract: Despite new classification nomenclature, there appears to be no identifiable prognostic implications for sarcomas that remain in the unclassifiable HGUPS group, as compared to the previously accepted MFH group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…21,22 This agrees with a prior SEER report of all patients with RPS, irrespective of tumor grade, which showed that adjuvant RT was associated with an increase in OS only in patients with malignant fibrous histiocytoma (although it should be noted that, in 2002, the World Health Organization declassified malignant fibrous histiocytoma and replaced it with high-grade undifferentiated pleomorphic sarcoma). 9,34 Of note, in our analysis of OS (Fig. 1), survival between the adjuvant RT and no RT groups is clearly divergent at the median OS but the difference between the groups seems to narrow significantly by approximately 80 months of follow-up.…”
Section: Discussionmentioning
confidence: 65%
“…21,22 This agrees with a prior SEER report of all patients with RPS, irrespective of tumor grade, which showed that adjuvant RT was associated with an increase in OS only in patients with malignant fibrous histiocytoma (although it should be noted that, in 2002, the World Health Organization declassified malignant fibrous histiocytoma and replaced it with high-grade undifferentiated pleomorphic sarcoma). 9,34 Of note, in our analysis of OS (Fig. 1), survival between the adjuvant RT and no RT groups is clearly divergent at the median OS but the difference between the groups seems to narrow significantly by approximately 80 months of follow-up.…”
Section: Discussionmentioning
confidence: 65%
“…One of the most common of these was malignant fibrous histiocytoma (MFH), a classification that has been rendered obsolete over the past decade. The majority of MFH in the retroperitoneum are now recognized and reclassified as undifferentiated pleomorphic sarcomas (UPS) or dedifferentiated liposarcomas (DDLPS), and correctly reclassifying an MFH/UPS into a DDLPS may require molecular testing . Additionally, the 7th edition of the American Joint Committee on Cancer changed the grading criteria for sarcomas from a four to a three‐grade system, classifying sarcomas as low, intermediate, and high grade .…”
Section: Introductionmentioning
confidence: 99%
“…Despite aggressive surgery, local recurrences occur in 13–42% of patients and nearly 31–35% will develop metastatic disease. 24 Although the addition of chemotherapy has shown some benefit in meta-analyses, these responses are marginal at best, highlighting the need for improved therapeutic options for UPS patients. 5,6 The use of radiation therapy is associated with reduced local recurrences in high grade sarcomas; however, approximately 3–5% of UPS arise in a prior site of therapeutic radiation for an unrelated malignancy and are termed radiation-associated UPS (RA-UPS), making radiation therapy controversial in this subset of the patients due to the comorbidities of re-irradiation 7,8 .…”
Section: Introductionmentioning
confidence: 99%